Community Canvas: How Public Art Transforms Urban Environments - Yi-Xuan, Liang; Wei-Jie, Wang (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
With the integration of global economy, the urbanization process in Rwanda develops rapidly. It appears particularly important to build city image. As manifestation of city characteristics, it reflects spiritual outlook of a city. Public art has participated in the process of transforming the aesthetics and symbolic meanings of civic centers across the country, even though for the most part its creative potential has been curtailed by the priority of urban planning and architecture as shapers of civic space. This research study discusses the role of public art in influencing urban environments in Rwanda, specifically within Kigali Cultural Village. The study explores the extent to which such an approach can raise local communities’ environmental awareness as an indirect input to the process of upgrading the desires of those living in these areas and of international tourists. In addition, it reviews the experiences of different types of catalysts for regeneration, such as art and culture that can enhance the built environment’s recognition, value, and economic growth. A qualitative evaluation is employed for this research study, which leverages subjective methods such as, consulting research papers and articles, interviews and observations to collect substantive and relevant data while examining the interaction of connectivity, attraction, and development as they relate to economics and other complex aspects of development. The findings reveal the main advantages of introducing public art to an urban space, namely in regard to acceptance, culture, and social behavior. In addition, the study helps identify new ways to use public art to enhance public interactions and participation in new urban environments development